PENDAMPINGAN ORANG TUA DAN GURU STIMULASI LITERASI PADA ANAK USIA DINI DI PAUD MEKARSARI DI KELURAHAN KRANJI KABUPATEN BANYUMAS - Johar Mamuri; Emiraldo Win Pazqara; Oti Kusumaningsih (Department of Public Administration, University Wijaykusuma Purwokerto, 2024)
This community service is carried out with the aim of providing understanding for parents and teachers regarding literacy, interest in reading for students at Merkarsari Early Childhood. This is done to build awareness among parents and teachers of the importance of literacy culture for early childhood. Training is carried out by providing education. about the importance of stimulating literacy in early childhood. The resulting output is to build the development of literacy culture in early childhood as one of the efforts to create educational institutions and other related institutions so that they can optimize early childhood development.